Optimal Fiscal Policy without Commitment: Revisiting Lucas-Stokey - Debortoli, Davide; Nunes, Ricardo; Yared, Pierre (Journal of Political Economy, 2021)
According to the Lucas-Stokey result, a government can structure its debt maturity to guarantee commitment to optimal fiscal policy by future governments. In this paper, we overturn this conclusion, showing that it does not generally hold in the same model and under the same definition of time consistency as in Lucas-Stokey. Our argument rests on the existence of an overlooked commitment problem that cannot be remedied with debt maturity: a government in the future will not necessarily tax above the peak of the Laffer curve, even if it is ex ante optimal to do so.